A Review of Drowning Prevention Interventions for Children and Young People in High, Low and Middle Income Countries. - Leavy, Justine; Crawford, Gemma; Leaversuch, Francene; Nimmo, L.; McCausland, Kahlia; Jancey, Jonine (2015)
Globally, drowning is one of the ten leading causes of child mortality. Children aged <5 years are particularly at risk, and children and young people continue to be overrepresented in drowning statistics. Accordingly, evidence informed interventions to prevent children drowning are of global importance. This review aimed to identify, assess and analyse public health interventions to reduce child drowning and investigate the use of behavioural theories and evaluation frameworks to guide child drowning prevention. Thirteen databases were searched for relevant peer reviewed articles. The systematic review was guided by the PRISMA criteria and registered with PROSPERO. Fifteen articles were included in the final review. Studies were delivered in high, middle and low income countries. Intervention designs varied, one-third of studies targeted children under five. Almost half of the studies relied on education and information to reduce drowning deaths, only three studies used a multi-strategy approach. Minimal use of behavioural theories and/or frameworks was found and just one-third of the studies described formative evaluation. This review reveals an over reliance on education and information as a strategy to prevent drowning, despite evidence for comprehensive multi-strategy approaches. Accordingly, interventions must be supported that use a range of strategies, are shaped by theory and planning and evaluation frameworks, and are robust in intervention design, delivery and evaluation methodology. This approach will provide sound evidence that can be disseminated to inform future practice and policy for drowning prevention.